IKs Activator ML277 Mildly Affects Repolarization and Arrhythmic Outcome in the CAVB Dog Model - Joanne J. A. van Bavel; Henriëtte D. M. Beekman; Agnieszka Smoczyńska; Marcel A. G. van der Heyden; Marc A. Vos (Biomedicines, 2023)
Long QT syndrome type 1 with affected IKs is associated with a high risk for developing Torsade de Pointes (TdP) arrhythmias and eventually sudden cardiac death. Therefore, it is of high interest to explore drugs that target IKs as antiarrhythmics. We examined the antiarrhythmic effect of IKs channel activator ML277 in the chronic atrioventricular block (CAVB) dog model. TdP arrhythmia sensitivity was tested in anesthetized mongrel dogs (n = 7) with CAVB in series: (1) induction experiment at 4 ± 2 weeks CAVB: TdP arrhythmias were induced with our standardized protocol using dofetilide (0.025 mg/kg), and (2) prevention experiment at 10 ± 2 weeks CAVB: the antiarrhythmic effect of ML277 (0.6–1.0 mg/kg) was tested by infusion for 5 min preceding dofetilide. ML277: (1) temporarily prevented repolarization prolongation induced by dofetilide (QTc: 538 ± 65 ms at induction vs. 393 ± 18 ms at prevention, p < 0.05), (2) delayed the occurrence of the first arrhythmic event upon dofetilide (from 129 ± 28 s to 180 ± 51 s, p < 0.05), and (3) decreased the arrhythmic outcome with a significant reduction in the number of TdP arrhythmias, TdP score, arrhythmia score and total arrhythmic events (from 669 ± 132 to 401 ± 228, p < 0.05). IKs channel activation by ML277 temporarily suppressed QT interval prolongation, delayed the occurrence of the first arrhythmic event and reduced the arrhythmic outcome in the CAVB dog model.